SILSILAH DALAM MATIUS 1:1-17 MENEGUHKAN YESUS SEBAGAI MESIAS - Fenius Gulo (STT Saint Paul Bandung, 2021)
The Gospel of Matthew 1: 1-17 records the genealogy of Jesus, the words of God who became flesh. Therefore, this reading tells only about the genealogy of Jesus, that is often neglected and considered not important to be learned. However, the author considers that the genealogy of Jesus in Matthew 1: 1-17 is very important. Based on an investigation of this genealogy, it is confirmed that Jesus is the fulfillment of the Messiah who was promised by God in the Old Testament period.